TINDAK PIDANA PENEBANGAN POHON DI TANAH ULAYAT MASYARAKAT ADAT DALAM KAWASAN HUTAN KONSERVASI CAGAR ALAM MANINJAU (Studi Kasus Nomor: 129/ Pid.B/ LH/ 2017/ PN. LBB) - Trisna, Nila; Husnaini, Husnaini; Yuana, Adella (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
In Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction, in this case, it does not pay attention to the rights of indigenous peoples who have obtained customary rights or rights to control forests for generations. In Nagari Koto Malintang, they have local wisdom that they have practiced for years, such as felling 2 trees for basic needs and not for commercial purposes through permission from local traditional leaders and the Wali Nagari Koto Malintang.This research is a normative juridical research using a case approach and a statute approach, in this research the analysis is carried out by criticizing, supporting, or commenting, then making a conclusion on the results of the study with their own thoughts. and literature review assistance.The application of material punishment in decision number 129/Pid. B/LH/2017/PN.LBB, According to the author, it is not appropriate and does not meet the elements charged by the public prosecutor, but in the judge's consideration of the aggravating circumstances, the panel of judges did not reflect a sense of justice towards the defendants and the values of local wisdom who have lived and run in the community for many years. The judge's consideration in this case also contradicts the theory of criminal responsibility in which the defendants can be given excuses for forgiveness and the ultimum theory remediates that punishment is the last step.Law Enforcement Officials should be wiser in eradicating the crime of logging trees on customary lands of customary law communities and must pay attention to the values that live in local communities such as local wisdom that they have practiced for years.